DETERMINASI KOMUNIKASI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI - I Komang Sudarsana; I Nengah Aristana; Yulius Geras (Universitas Triatma Mulya, 2021)
The purpose of this research: (1) to determine the effect of communication (X1) on employee performance (Y) in the Department of Public Works and Spatial Planning in Southwest Sumba Regency, (2) to determine the effect of leadership (X2) on employee performance (Y) in the Department of Public Works and Spatial Planning of Southwest Sumba Regency, (3) to find out the independent variables that have a dominant influence on employee performance in the Department of Public Works and Spatial Planning of Southwest Sumba Regency, (4) to determine the magnitude of the influence of communication and leadership on employee performance at the Department of Public Works and Spatial Planning in Southwest Sumba Regency. The population in this study are employees of the Department of Public Works and Spatial Planning in Southwest Sumba Regency, while determining the sample using the Slovin formula so that the samples obtained were as many as 90 people. Data analysis techniques used were quantitative descriptive analysis, validity and reliability tests, classic assumption tests, multiple linear regression analysis, partial tests, and determination analysis. The analysis shows the regression model Y = 1.545 + 0.205X1 + 0.550X2. The conclusion obtained is communication (X1) has a positive and significant effect on employee performance variables (Y) in the Department of Public Works and Spatial Planning in Southwest Sumba Regency, which is indicated by the regression coefficient b1X1 which is positive. Leadership (X2) has a positive and significant effect on employee performance variables (Y) in the Department of Public Works and Spatial Planning in Southwest Sumba Regency, which is indicated by the positive coefficient b2X2 regression coefficient. The independent variable that has a dominant influence on employee performance is the leadership variable (X2) that is 0.550 while the communication variable (X1) is 0.205. The magnitude of the influence of communication and leadership on employee performance at the Department of Public Works and Spatial Planning in Southwest Sumba is 78.2% while the remaining 21.8% is influenced by other variables outside of this study.